Hubungan Jangka Pendek dan Jangka Panjang antara Pembiayaan Perbankan Syariah dan GDP di Indonesia dengan menggunakan metode Vector Error Correction Model - Zul Ihsan Mu'arrif (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research analyzes the relationship between Islamic bank financing and economic growth as measured by Gross Domestic Product (GDP) using the Vector Error Correction Model (VECM) to explain the short-term and long-term relationship dynamics between these two variables. The results of this research found that there is a long-term negative relationship between Islamic bank financing and GDP. These findings indicate that, although Sharia financing is expected to support economic growth through Sharia-based financial principles, the reality shows that the direct effect on overall economic growth is more complex and not always unidirectional. Apart from that, this research also finds that in the short term, both sharia financing and GDP adjust back to long-term balance after experiencing deviations, which means a strong economic correction mechanism exists. The stable VAR stability test results validate the model's reliability in describing the accurate relationship between sharia financing and economic growth in Indonesia. These findings provide important insights for policymakers and Islamic banking practitioners in developing more effective strategies to encourage inclusive economic growth.